Odpowiedzi

Najlepsza Odpowiedź!
2010-03-18T15:33:49+01:00
-7,23+14 i 1/4 +(-8,02)=-7,23+14,25-8,02=7,02-8,02= - 1
-42,7+(-13,6)+12,7=-42,7-13,6+12,7= -56,3+12,7= -43,6
3*(-2/3)=3/1*(-2/3)= -2
-4*(-1,1)=4,4
(-13+8)*(-2)=-5*(-2)=10
(3-7+2)³ =(-2)³ = -8






2010-03-18T15:37:08+01:00
-7,23 + 14 ,(jedna czwarta) + (-8,02) =
-7,23+14,25-8,02 =
-1


-42,7 + (-13,6)+12,7 =
-42,7-13,6+12,7 =
-43,6


3 (razy) (- dwie trzecie)
3*(-⅔) =
-2


(-4) * (-1,1) =
4,4


(-13 +8) * (-2) =
(-5)*(-2) =
10


(3-7 + 2) do potęgi 3 =
(-2)³ =
-8